A model for measuring weil-being of medical practitioners in EHR implementation - Ahmad, Maznah; Kartiwi, Mira (Institute of Electrical and Electronics Engineers Inc., 2017)
When healthcare institutions decide to implement electronic health records (EHR) to improve healthcare administrative processes and reduce medical errors, it may canse major alterations in varions clinical work processes. Thns, the implementation of EHR wonld nsnally lead to the resistance of the healthcare practitioners since they may look at the system as hindrance to their effective clinical work. The practitioners in the hospitals nsnally face difficulties and obstacles in spite of the many benefits promised by EHR such as the inconvenience of having to key in data during patient consultation the need to carry their laptops to inappropriate places. Since there has not been much investigation done on The implementation process of the system and its impact within the healthcare institutions, especially in Malaysia, this study seeks to investigate the influence of EHR in the selected Malaysian healthcare institutions on the wellbeing of healthcare practitioners using a case study approach. While identifying the different models of implementation being used in the selected institutions, the study proceeded to examine whether the implementation process impacts system service quality and their satisfaction using the EHR system influence their personal wellbeing.